2011
DOI: 10.1080/01496395.2011.595757
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Modeling of Arsenic Removal from Water by Ferric Ion Loaded Red Mud

Abstract: A laboratory study was conducted to investigate the ability of ferric ion loaded red mud (FRM) for the removal of arsenic species from water. The adsorbent material was characterized by scanning electron microscopy, X-ray diffraction, and Fourier transform infrared spectroscopy. For an initial arsenic concentration lower than 0.3 mg/L, the FRM with a dosage of 1 g/L was able to reduce As(III) at pH 7 below 10 lg=L, the maximum contaminant level (MCL) of arsenic in drinking water set by the World Health Organiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 47 publications
1
7
1
Order By: Relevance
“…The thickness of boundary layer given by the intercept correspond to 6.5 and 11.1 mg/g for 20% and 5% FeEPS. Contrary to what observed by other authors [39,41], the lack of an initial stage related to film diffusion suggested that boundary layer was not limiting in our case. We finally hypothesize that at the same time EPS may exert repulsion with As ions but also facilitate the entrapment into the gel by EPS polysaccharides driven chelation and speeding up the adsorption process, as evidenced by higher adsorption rate during first minutes, in line with what evidenced for positively charged potentially toxic metals [30].…”
Section: Kinetic Behaviour Of Feepscontrasting
confidence: 99%
See 1 more Smart Citation
“…The thickness of boundary layer given by the intercept correspond to 6.5 and 11.1 mg/g for 20% and 5% FeEPS. Contrary to what observed by other authors [39,41], the lack of an initial stage related to film diffusion suggested that boundary layer was not limiting in our case. We finally hypothesize that at the same time EPS may exert repulsion with As ions but also facilitate the entrapment into the gel by EPS polysaccharides driven chelation and speeding up the adsorption process, as evidenced by higher adsorption rate during first minutes, in line with what evidenced for positively charged potentially toxic metals [30].…”
Section: Kinetic Behaviour Of Feepscontrasting
confidence: 99%
“…Several kinetics and thermodynamics models to describe arsenic adsorption processes have been previously reported [37][38][39][40][41].…”
Section: Adsorption Modelsmentioning
confidence: 99%
“…Similarly, Tawabini et al [48] reported maximum percent removal of As(III) at pH 7 and 8 and decrease in adsorption at pH 9 for iron oxide nanoparticles impregnated on carbon nanotubes. Moreover, Kocabas and Yurum [49] observed maximum adsorption of As(III) at pH 7.56 by Ferric ion loaded red mud.…”
Section: -mentioning
confidence: 95%
“…Adsorption is the most widely used process due to the simplicity of its operation and low implementation costs when compared with other treatment methods [1]. Adsorbent 2 Advances in Materials Science and Engineering substances, most commonly used to remove heavy metals from water, are activated carbon, ion exchange resins, red clay, activated alumina, biomass, and chitosan and carbon nanotubes [7,[13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%